KINERJA BELANJA PADA KANTOR DESA LOA DURI ULU KECAMATAN LOA JANAN - Taghfirul Azhima Yoga Siswa3, Melinda Titin Ruliana (EKONOMIA, 2020)
The purpose of this study is ? a. To find out the spending performance of the 2016-2017 fiscal year in terms of analysis of variance in the village office of Loa Duri Ulu, Loa Janan Subdistrict, it is classified as poor, b. To find out the spending performance of the 2016-2017 fiscal year in terms of the analysis of expenditure growth in the Loa Duri Ulu village office, Loa Janan Subdistrict is classified as negative, c. To find out the spending performance of the 2016-2017 fiscal year in terms of the analysis of expenditure conformity which consists of operational expenditure ratios and capital expenditure ratios in the Loa Duri Ulu village office, Loa Janan Subdistrict is classified as mismatched, d. To find out the spending performance of the 2016-2017 fiscal year in terms of the efficiency ratio at the Loa Duri Ulu village office in Loa Janan Subdistrict, it is classified as less efficient. The analytical tool used is shopping analysis which consists of variant shopping analysis, analysis of shopping growth, expenditure compatibility analysis and efficiency ratio. The results of the analysis put forward can be seen that, a. Shopping performance in the 2016-2017 fiscal year in terms of variance analysis at the Loa Duri Ulu village office in Loa Janan District is relatively good, with the realization of spending smaller than the budget so that the first hypothesis is rejected, b. Shopping performance in the 2016-2017 fiscal year in terms of the analysis of expenditure growth at the Loa Duri Ulu village office in Loa Janan Subdistrict is classified as negative with the criteria decreasing so that the second hypothesis is accepted, c. Shopping performance in the 2016-2017 fiscal year in terms of the analysis of expenditure compatibility at the Loa Duri Ulu village office in Loa Janan Subdistrict is classified as inconsistent with the criteria of 20 - 40%, so that the hypothesis is accepted, d. Shopping performance in the 2016-2017 fiscal year in terms of efficiency ratio at the Loa Duri Ulu village office in Loa Janan Subdistrict is classified as efficient with 90 - 100% assessment criteria up to 80 - 90%, so the fourth hypothesis is rejected.